The Effectiveness of ICT-Based Academic Supervision Model in Improving Teachers' Professional Competence at Santa Lusia Kindergarten, Archdiocese of Medan - Banjarnahor, Saloma; Rahman, Arif; Daryanto, Eka (RIRAI Publisher, 2024)
The research aims to accomplish three main things: first, to create a model for academic supervision that uses Information and Communication Technology (ICT) and website media to improve the professional competence of Santa Lusia Kindergarten teachers in Keuskupan Agung Medan. Second, to determine if the model can be implemented and evaluated in this educational setting. Third, to implement and evaluate the model. Making sure the model is feasible and usable in the real world is the main goal of the study. The result show that ICT-based academic supervision model that was developed proved effective in improving the professional competence of teachers at TK Santa Lusia. The N-Gain test results in cycle II, which reached 0.723 (72.34%), demonstrated the model's effectiveness, although it slightly decreased from cycle I (73.30%). With N-Gain values ranging from 46.15% to 88.89%, the model consistently provided significant improvements in teacher competence. The results indicate that the model effectively enhances teacher professional competence at Santa Lusia Kindergarten in Keuskupan Agung Medan.